2014
DOI: 10.1007/s11356-014-3075-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lymantria dispar affected by manganese in food

Abstract: We studied the response of gypsy moth (Lymantria dispar (Linnaeus) (Lepidoptera: Lymantriidae)) to the content of manganese in food in the laboratory breeding of caterpillars. The food of the caterpillars {Betula pendula Roth (Fagales: Betulaceae) leaves} was contaminated by dipping in the solution of MnCl2 · 4H2O with manganese concentrations of 0, 0.5, 5 and 10 mg ml(-1), by which differentiated manganese contents (307; 632; 4,087 and 8,124 mg kg(-1)) were reached. Parameters recorded during the rearing were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Manganese is an essential co-factor in many enzymes but can impact insect behavior at low doses and, like all metals, is toxic in excess (Ben-Shahar 2018). Caterpillars of Lymantria dispar and Cabera pusaria have been shown to excrete excess Mn through frass and molting (Kula et al . 2014, Martinek et al .…”
Section: Discussionmentioning
confidence: 99%
“…Manganese is an essential co-factor in many enzymes but can impact insect behavior at low doses and, like all metals, is toxic in excess (Ben-Shahar 2018). Caterpillars of Lymantria dispar and Cabera pusaria have been shown to excrete excess Mn through frass and molting (Kula et al . 2014, Martinek et al .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that P. arborator avoided manganese intoxication through food by releasing manganese into the feces or by neutralizing manganese in relatively high concentrations. Kula et al (2014) studied the reaction of Lymantria dispar (Linnaeus, 1758) to the content of manganese in food during laboratory breeding of the caterpillars. The caterpillars were fed with leaves of birch soaked in solutions of MnCl 2 at concentrations of 0, 0.5, 5 and 10 mg kg -1 , the content of manganese equaled 307, 632, 4,087 and 8,124 mg kg -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Although essential, chronic dietary exposure to Mn is often toxic and detrimental to the fitness of most arthropod species, including insects, via effects on embryonic development, feeding behaviors, reproduction, immunity, and general survivability ( Olsén, 2011 ; Kula et al, 2014 ; Ternes et al, 2014 ; de Barros et al, 2017 ; Martinek et al, 2018 ). For example, the collembolan Folsomia candida is highly sensitive to Mn in its diet ( Kuperman et al, 2004 ).…”
Section: Manganese and Insect Biologymentioning
confidence: 99%
“…However, other arthropods, such as the fly Megaselia scalaris , show few adverse effects of Mn exposure, even at levels as high as 2,600 mg Mn/kg ( Sorensen et al, 2009 ). While the exact mechanisms that affect the sensitivity threshold of insects to Mn exposure are mostly unknown, studies suggest that some species can actively avoid the consumption of Mn-contaminated foods ( Rokytova et al, 2004 ), while others evolved mechanisms for efficient excretion of dietary Mn and/or its sequestration in specific body parts ( Kula et al, 2014 ; Martinek et al, 2017 , 2018 ).…”
Section: Manganese and Insect Biologymentioning
confidence: 99%